2020
DOI: 10.3390/app10249025
|View full text |Cite
|
Sign up to set email alerts
|

Association between Rapid Maxillary Expansion and Nocturnal Enuresis in Children: A Pilot Study for a Randomized Controlled Clinical Trial

Abstract: Objectives: This pilot study was conducted to test the protocol of a randomized controlled trial evaluating whether rapid maxillary expansion (RME) can relieve nocturnal enuresis (NE) and improve breathing in children, after ruling out a placebo effect, and investigating whether the effects of RME and NE are related to the morphology of the upper airway. Methods: Seventy 6–15-year-old patients with NE were assessed for eligibility (e.g., constricted maxilla). Enrolled subjects were randomized to immediate trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The hypothesis was that RME treatment would lead to a reduction in nocturnal urine production as a result of improved breathing obtained by enlarging the nasal and pharyngeal airway. The authors suggested that RME reduces the frequency of NE and that there might be an association between the amount of expansion and the reduction in night urine volume [14].…”
Section: Special Issue Evidencementioning
confidence: 99%
“…The hypothesis was that RME treatment would lead to a reduction in nocturnal urine production as a result of improved breathing obtained by enlarging the nasal and pharyngeal airway. The authors suggested that RME reduces the frequency of NE and that there might be an association between the amount of expansion and the reduction in night urine volume [14].…”
Section: Special Issue Evidencementioning
confidence: 99%